An Analysis of the Operational Efficiency of Massage and SPA Businesses on Asian Highway Number 15 - UEASIN, Nattanin (Journal of Environmental Management and Tourism, 2017)
The objectives of this study are (1) to study and compare the characteristics of Thai massage and spa industries in three provinces on the Asian Highway number 15 (AH15) and (2) to measure and compare the operational efficiency of massage and spa industries of the three provinces in Thailand that are on AH15. The study collected data in 2015 - 2016 with questionnaires from a total of 95 firms. The results revealed that the businesses in all three provinces had a small number of employees at around 1-5 persons, together with a small number of beds (1-5 beds). However, there were some large-scale spa and massage business on operating in every province that were fully equipped with many facilities and products for customers. The operational efficiency of massage and spas were subject to a regional frontier showing that Sakon-Nakhon had an average score of 0.947, followed by Nakhon Phanom and Udontani with average scores of 0.885 and 0.778, respectively. The research suggests that a business should support employees in order to increase productivity and labor skills. Initial investment should be employed carefully and economically so as to enhance operational efficiency. Moreover, the variety of massage training programs, music for relaxation, cleanliness and noise reduction are main strategies to increase customer satisfaction.